Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.5005/jp-journals-10071-24075
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 and Its Correlation with COVID-19 in Terms of Outcomes in an Intensive Care Unit of a Rural Hospital: A Cross-sectional Study

Abstract: A bstract Background Interleukin 6 (IL-6) encoded by the gene coded as IL 6 acts as a proinflammatory cytokine as well as an anti-inflammatory myokine. It is postulated that IL 6 is associated directly with the severity of coronavirus disease-2019 (COVID-19). Another domain that is thought to predict the severity of COVID-19 is the neutrophil:lymphocyte (N:L) ratio; a higher N:L ratio is postulated to be related to more severe outcomes. Thus, the present study was aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
(8 reference statements)
3
5
1
Order By: Relevance
“…[ 37 ] However, in this analysis, critical patients are not considered separately. By contrast to our results, a study conducted in the ICU of a rural hospital in India demonstrated no association between IL-6 and clinical outcomes [ 38 ]. This contradictory finding highlights the need for larger, multicentric studies investigating the predictive value of inflammatory biomarkers in critical COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 37 ] However, in this analysis, critical patients are not considered separately. By contrast to our results, a study conducted in the ICU of a rural hospital in India demonstrated no association between IL-6 and clinical outcomes [ 38 ]. This contradictory finding highlights the need for larger, multicentric studies investigating the predictive value of inflammatory biomarkers in critical COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 99%
“…This study also shows that the level of IL-6 increases in seriously ill patients and in the cases of unfavorable outcomes and it is correlated with the severity and death in patients ( Table 2 , Table 5 , Table 6 and Table 7 , Figure 1 , Figure 2 and Figure 3 ). Our results are consistent with the research of other authors evaluating the prognostic significance of IL-6 in COVID-19 infections [ 37 ]. For example, in a retrospective single-center study conducted on 728 patients with COVID-19, the prognostic significance of elevated IL-6 levels for assessing mortality and a severe disease course was studied [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, cytokine mRNA levels were high in the lung of cases with very short disease course ( Supplementary Table S2 ), whereas no significant levels were detected in the other patients, congruent with a decrease in serum IL-6 levels before death. 32 This finding suggests that the massive secretion of cytokines occurs early in disease, but it should not be considered a reliable marker of disease severity due to its transiency. In fact, the increase of cytokine is rapidly followed by high and durable expression of P-selectin at tissue level in all stages of disease, representing a hallmark of COVID-19 cases.…”
Section: Resultsmentioning
confidence: 99%